Calycosin stimulates the osteogenic differentiation of rat calvarial osteoblasts by activating the IGF1R/PI3K/Akt signaling pathway. (29th January 2019) - Fang, Yaoyao; Xue, Zhiyuan; Zhao, Lianggong; Yang, Xiuyan; Yang, Yafei; Zhou, Xianglin; Feng, Shilan; Chen, Keming
Abstract: Calycosin has been reported to have a strong osteogenic activity and a positive correlation with anti‐osteoporosis effects. However, its precise mechanism of action remains unclear. Since insulin‐like growth factor 1 receptor (IGF1R) signaling and phosphatidylinositol 3‐kinase/Akt (PI3K/Akt) signaling have been shown to play a pivotal role in regulating osteogenesis, we hypothesized that the osteogenic activity of calycosin is mediated by these signaling pathways. Rat calvarial osteoblasts (ROBs) were cultured in osteogenic medium containing calycosin with or without GSK1904529A (GSK) or LY294002 (LY) (inhibitors of IGF1R and PI3K, respectively). The effects on cell proliferation, alkaline phosphatase (ALP) activity, calcified nodules, mRNA or protein expression of osteogenic genes [alkaline phosphatase ( Alpl ), collagen type I ( Col1a1 ), runt‐related transcription factor 2 ( Runx2 ), Osterix, and bone morphogenetic protein 2 ( Bmp2 )], and phosphorylation of IGF1R and Akt were examined. The present results showed that calycosin enhanced cell proliferation, ALP activity and Alizarin Red‐S staining in a dose‐dependent manner in the range of 10 −8 –10 −6  M, while an inhibitory effect was observed at 10 −5  M. Treatment at the optimal concentration (10 −6  M, a physiologically achievable concentration) increased mRNA levels of osteogenic genes and phosphorylation of IGF1R and Akt. Furthermore, treatment with GSK or LY partly reversed the effects of calycosin on ROBs, as indicated by the decreases in calycosin‐induced ALP activity, calcified nodules and osteogenic gene expression. These results suggest that the osteogenic effect of calycosin partly involves the IGF1R/PI3K/Akt signaling pathway.